2009
DOI: 10.1128/jvi.00926-09
|View full text |Cite
|
Sign up to set email alerts
|

Elastase-Dependent Live Attenuated Swine Influenza A Viruses Are Immunogenic and Confer Protection against Swine Influenza A Virus Infection in Pigs

Abstract: Influenza A viruses cause significant morbidity in swine, resulting in a substantial economic burden. Swine influenza virus (SIV) infection also poses important human public health concerns. Vaccination is the primary method for the prevention of influenza virus infection. Previously, we generated two elastase-dependent mutant SIVs derived from A/Sw/Saskatchewan/18789/02(H1N1): A/Sw/Sk-R345V (R345V) and A/Sw/Sk-R345A (R345A). These two viruses are highly attenuated in pigs, making them good candidates for a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 50 publications
0
52
0
Order By: Relevance
“…These LAIV are attenuated based on the incorporation of cold-adapted (ca) and/or temperature sensitive (ts) phenotypes into vaccine strains by recombination with a donor strain or by multiple passages of the vaccine strain at low temperatures (47)(48)(49). Several different experimental live attenuated SIV vaccines have been demonstrated to induce strong cell-mediated immunity (CMI) and humoral immunity, as well as cross-protection against homologous heterotypic and heterologous SIV isolates (11,16). Even though these experimental SIV LAIV have advantages over their inactivated counterparts, no LAIV is currently registered for use against SIV infections worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These LAIV are attenuated based on the incorporation of cold-adapted (ca) and/or temperature sensitive (ts) phenotypes into vaccine strains by recombination with a donor strain or by multiple passages of the vaccine strain at low temperatures (47)(48)(49). Several different experimental live attenuated SIV vaccines have been demonstrated to induce strong cell-mediated immunity (CMI) and humoral immunity, as well as cross-protection against homologous heterotypic and heterologous SIV isolates (11,16). Even though these experimental SIV LAIV have advantages over their inactivated counterparts, no LAIV is currently registered for use against SIV infections worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Pena et al generated a recombinant influenza virus by rearranging the genome of an avian H9N2 virus and expressed the entire H5 HA ORF from the NS segment RNA (54). All these results suggest the possibility and feasibility of rescuing influenza A viruses by replacing the coding region of HA, NA, or other influenza virus Previous studies demonstrated that an elastase-dependent SIV could be used as a LAIV against homologous, homologous heterotypic, and heterologous SIV isolates (11,14). Despite the significant protective efficacy against parental and homotypic SIVs, only partial protection was elicited against the heterologous H3N2 subtype.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations